High energy rectangular pulse generated in a low repetition rate all normal-dispersion Yb3+-doped fiber laser. (26th February 2015) - Lin, Ja-Hon; Lai, Beng-Cheng; Lee, Yin-Wen
Abstract: With elongated cavity length, a 317 kHz low-repetition-rate rectangular pulse was demonstrated in an all-normal dispersion mode-locked (ML) ytterbium-doped fiber laser (YDFL) based on the nonlinear polarization evolution technique. As the pump power increased, the duration of the rectangular pulse broadened linearly without wave-breaking. At a maximum pump power of 240 mW, a rectangular pulse with a duration of 20.5 ns and highest pulse energy of 182 nJ was produced. Through an Yb 3+ -doped fiber amplifier with 4 W pump power, the energy of the rectangular pulse was further amplified up to 2.28  µ J. The duration of the rectangular pulse remained constant as the pump energy increased and revealed no pulse distortion under the maximum output energy.